The accuracy of neutrophil to lymphocyte ratio and platelet to lymphocyte ratio as a marker for gastrointestinal malignancies - Nora, Ian (J Gastrointest Oncol, 2018)
BACKGROUND: Accurate predictors of locally advanced and recurrence disease in patients with gastrointestinal cancer are currently lacking. Neutrophil to lymphocyte ratio (NLR) and platelet to lymphocyte ratio (PLR) have emerged as possible markers for predicting recurrence in these patients. In this study, we sought to evaluate the utility of NLR and PLR in predicting the presence of regional nodal disease, metastasis and systemic recurrence in patients with gastrointestinal malignancies. METHODS: We queried a comprehensive gastrointestinal oncology database to identify patients who had undergone surgery for a GI malignancy. NLR and PLR values were determined via a complete blood count (CBC). In patients treated with neoadjuvant therapy (NT) the NLR and PLR were calculated from CBCs before and after NT and in patients proceeding to surgery within 2 weeks pre-operatively. The associations between NLR and PLR and the clinicopathologic parameters (sex, age, tumor size, differentiation, positive lymph nodes, and metastatic disease) were assessed via χ(2) or Fisher’s exact tests where appropriate. All the tests were two-sided, and P<0.05 was considered statistically significant. RESULTS: We identified 116 patients diagnosed with gastrointestinal malignancies. There were 76 (65.5%) males and 40 (34.5%) females with an average age of 69.4±10.7 years. The mean follow up was 14.1±15.5 months. We identified 49 (42.2%) esophageal, 34 (29.3%) pancreatic, 14 (12.1%) colorectal, 13 (11.2%) gastric, and 6 (5.2%) biliary cancers. There were 36 (31.0%) patients with node negative disease, 52 (44.8%) with node positive and 28 (24.2%) with metastatic disease at surgery. Of the metastatic patients 4 (3.4%) were found at staging laparoscopy and 24 (20.6%) were diagnosed pre-operatively. The median NLR for LN− patient’s was 1.78 (0.23–8.2) and for LN+ and metastatic patients was 4.69 (2.27–36), P<0.001. The median PLR for LN– patient’s was 123.03 (14–257.69) and for LN+ and metastatic patients was 212.42 (105.45–2,185.18), P<0.001. The sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) for a NLR >2.25 was 98.8%, 72.2%, 89%, and 96% respectively. The sensitivity, specificity, PPV, and NPV for PLR >140 was 95%, 78%, 90%, and 88% respectively. Utilizing both NLR and PLR the sensitivity, specificity, PPV and NPV was increased. CONCLUSIONS: Elevation of NLR and PLR can be used to help identify patients with advanced disease GI malignancies and recurrences after surgery. Additionally, failure of normalization of NLR and PLR 3-month post-surgical resection may indicate early recurrence or persistent disease. Individually, NLR has a higher sensitivity and negative predictive value while PLR has a higher specificity and positive predictive value for distinguishing metastatic disease and node positivity. The combination of NLR and PLR has the highest accuracy of predicting advanced disease among all gastrointestinal malignancies.